Surgical Treatment of Cavus Foot in Charcot-Marie-Tooth Disease: A Review of Twenty-four Cases. (18th March 2015) - Faldini, Cesare; Traina, Francesco; Nanni, Matteo; Mazzotti, Antonio; Calamelli, Carlotta; Fabbri, Daniele; Pungetti, Camilla; Giannini, Sandro
Abstract : Abstract: Charcot-Marie-Tooth disease is the single most common diagnosis associated with cavus foot. The imbalance involving intrinsic and extrinsic muscles has been suggested as the main pathogenetic cause of cavus foot in this disease. The goal of surgical treatment is to correct the deformity to obtain a plantigrade foot. In the presence of a flexible deformity and the absence of degenerative arthritis, preserving as much as possible of the overall range of motion of the foot and ankle is advisable. Twenty-four cavus feet in twelve patients with Charcot-Marie-Tooth disease were included in the study. Clinical evaluation was summarized with the Maryland Foot Score. Radiographic evaluation assessed calcaneal pitch, Meary angle, Hibb angle, and absence of degenerative joint changes. Only patients who had a flexible deformity, with varus of the heel reducible in the Coleman-Andreasi test, and did not have degenerative joint arthritis were included in this study. Surgical treatment consisted in plantar fasciotomy, midtarsal osteotomy, extensor hallucis longus tendon transfer to the first metatarsal (Jones procedure), and dorsiflexion osteotomy of the first metatarsal. Mean follow-up was six years (range, two to thirteen years). The mean Maryland Foot Score was 72 preoperatively and 86 postoperatively. The postoperative result was rated as excellent in twelve feet (50%), good in ten (42%), and fair in two (8%). Mean calcaneal pitch was 34° preoperatively and 24° at the time of the latest follow-up, the mean Hibb angle was 121° preoperatively and 136° postoperatively, and the mean Meary angle was 25° preoperatively and 2° postoperatively. Plantar fasciotomy, midtarsal osteotomy, the Jones procedure, and dorsiflexion osteotomy of the first metatarsal yielded adequate correction of flexible cavus feet in patients with Charcot-Marie-Tooth disease in the absence of fixed hindfoot deformity. The fact that the improvement in the outcome score was only modest may be attributable to the lack of motor balance. Level of Evidence: TherapeuticLevel IV . See Instructions for Authors for a complete description of levels of evidence.